Pengaruh Kualitas Sistem Dan Layanan Terhadap Kepuasan Pengguna Aplikasi SIAPP di Kabupaten Sidenreng Rappang - Arham Sulma; Arya Zacky W (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2023)
The era of the Industrial Revolution 4.0 is a digital technology and the internet. For the sake of creating good governance, electronic government (e-government) is carried out. In carrying out an effective complaint service, the Office of Communication and Information (Diskominfo) of Sidenreng Rappang Regency developed an application for the Public Aspirations and Complaints Information System (SIAPP). However, the visible performance of SIAPP still needs to improve, and only a few incoming complaints. This study aims to determine the influence of system quality and service quality factors on SIAPP user satisfaction in Sidenreng Rappang Regency and their impact on efforts to improve SIAPP quality. This study uses a mixed methods research method with an explanatory sequential design. Quantitative sampling uses total sampling, and qualitative sampling uses purposive sampling with questionnaires, interviews, and documentation as data collection tools. The findings obtained by the authors in this study are that the system quality and service quality have a positive and significant influence on user satisfaction, either partially or simultaneously. However, there are still problems with systems and services that still need to be improved. The system's quality significantly and significantly affects user satisfaction by 17.28% with a low degree. Furthermore, service quality has a significant and significant effect on user satisfaction of 57.19% with a high degree. Then, the system quality and service quality together substantially affect user satisfaction by 74.5% with a high degree. The impact of these influences makes people feel comfortable and trust the government. On the other hand, Diskominfo will be more enthusiastic to improve the quality of SIAPP. To increase the role of SIAPP as a forum for aspirations, it is recommended to strengthen application features and the part of the admin and conduct socialization so that complaint services are more effective.